2020
DOI: 10.3389/fmicb.2020.584174
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiles Reveal the Growth-Promoting Mechanisms of Paenibacillus polymyxa YC0136 on Tobacco (Nicotiana tabacum L.)

Abstract: Paenibacillus polymyxa is an important member of the plant growth-promoting rhizobacteria. P. polymyxa YC0136 inoculation had beneficial effect on growth promotion and biological control of tobacco (Nicotiana tabacum L.) under field conditions. This study aimed to reveal the growth-promoting mechanisms of strain YC0136. In growthpromotion assays, tobacco plant height was increased by 8.42% and 8.25% at 60 and 90 days, respectively, after inoculation with strain YC0136. Strain YC0136 also promoted the accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 100 publications
4
37
1
Order By: Relevance
“…In response to host rice seedlings, Bacillus subtilis OKB105 also altered its transcriptomic patterns, in which 52 genes related to nutrients transport and metabolism were upregulated, suggesting the bacterium used carbohydrates and amino acids secreted by rice seedlings as carbon and energy sources. In contrast to the data in [ 163 ], many genes involved in chemotaxis and motility, however, were downregulated [ 173 ].…”
Section: Roles Of Multi-omics Techniques In Deciphering Plant–micrcontrasting
confidence: 95%
See 4 more Smart Citations
“…In response to host rice seedlings, Bacillus subtilis OKB105 also altered its transcriptomic patterns, in which 52 genes related to nutrients transport and metabolism were upregulated, suggesting the bacterium used carbohydrates and amino acids secreted by rice seedlings as carbon and energy sources. In contrast to the data in [ 163 ], many genes involved in chemotaxis and motility, however, were downregulated [ 173 ].…”
Section: Roles Of Multi-omics Techniques In Deciphering Plant–micrcontrasting
confidence: 95%
“…Malviya et al [ 170 ] also found that the infection of Burkholderia anthina MYSP113 into the sugarcane plantlets cv. GXB-9 induced the upregulation of phenylpropanoid biosynthesis genes and amino acid biosynthesis pathways, in accordance with the findings from Liu et al [ 163 ]. Likewise, phenylpropanoid biosynthesis was the most enriched pathway in both differentially expressed genes (DEGs) and abundant metabolites (DAMs) among all salt stress responses in barley rootzones [ 171 ].…”
Section: Roles Of Multi-omics Techniques In Deciphering Plant–micrsupporting
confidence: 91%
See 3 more Smart Citations